PERLINDUNGAN HUKUM PENYEWA RUSUNAWA JIKA TERJADI WANPRESTASI DALAM PERJANJIAN SEWA MENYEWA MENGENAI PERBUP NO.24 TAHUN 2018 TENTANG TARIF SEWA RUSUNAWA DI SIDOARJO PERSPEKTIF PERLINDUNGAN KONSUMEN - Salsabil, Firdani Alifia; Ahmad, Muh.Jufri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The definition of flats is contained in Law no. 20 of 2011 concerning Flats. Flats are buildings built in a limited space that are arranged functionally, both in horizontal and vertical orientation, used as residential areas equipped with the same facilities. Building flats is the government's plan to meet housing needs, especially in densely populated urban areas, these flats target people with low sweating (MBR). The Sidoarjo Regency Government is no exception. Rent for residential premises must be paid monthly, and prospective tenants must meet the requirements first. Rental flats in Sidoarjo Regency are regulated in Perbup No. 24 of 2018 concerning Flat Rental Rates in Sidoarjo Regency. The implementation of the rental flat agreement is a legal relationship that arises because of an agreement between the manager and the tenant, if the manager abuses the regulations without permission, what is the legal protection for the tenant? Law No. 8 of 1999 is a regulation that contains legal protection for tenants